2018
DOI: 10.1177/0194599818778502
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Industry Involvement in Otolaryngology: Insights from 3 Years of the Open Payments Database

Abstract: Objectives To characterize industry payments to otolaryngologists in 2016 versus 2014 and 2015. Study Design Cross-sectional retrospective analysis. Setting Open Payments Database. Subjects and Methods Using the Open Payments Database, we identified otolaryngologists receiving payments from industry sponsors from 2014 to 2016. We characterized the number and value of payments per physician overall and by census region, as well as by sponsor subspecialty and payment type. Study years were compared via analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 17 publications
4
30
4
Order By: Relevance
“…8,[11][12][13] We had previously identified a trend of increasing compensation in otolaryngology from 2014 to 2016, to a high of $14.5 million in 2016, that was not seen in the overall database or in other surgical and nonsurgical subspecialties. 8 In contrast to this, we found here that overall payment decreased from $14.5 million in 2016 to $11.2 million in 2017; however, that is still higher than $9.9 million in 2015. During this period, the value of general payments in the overall database was relatively constant, decreasing only slightly to $8.4 billion in 2017 from $8.8 billion in 2016 and $8.4 billion in 2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[11][12][13] We had previously identified a trend of increasing compensation in otolaryngology from 2014 to 2016, to a high of $14.5 million in 2016, that was not seen in the overall database or in other surgical and nonsurgical subspecialties. 8 In contrast to this, we found here that overall payment decreased from $14.5 million in 2016 to $11.2 million in 2017; however, that is still higher than $9.9 million in 2015. During this period, the value of general payments in the overall database was relatively constant, decreasing only slightly to $8.4 billion in 2017 from $8.8 billion in 2016 and $8.4 billion in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited to 3 years of data, we speculated that this may represent an overall trend of increased physician-industry interaction within otolaryngology. 8…”
mentioning
confidence: 99%
“…Orthopaedic surgeons have long maintained close relationships with industry, perhaps because of the importance of implants and surgical tools to orthopaedic procedures. Previous studies have assessed OPD payments in the surgical fields of cardiothoracic surgery, 6 neurosurgery, 7 otolaryngology, 13,14,17,18 plastic surgery, 19 and urology. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…13-15 For instance, in urology, it was found that the number of surgeons with industry relationships stayed similar, but total payments went down between 2014 and 2016. 13 Additionally, an evaluation of the OPD in plastic surgery showed a decrease in the number of plastic surgeons holding industry ties and a reduction in total payment from 2013 to 2014. 16 It has been hypothesized that increased public scrutiny afforded by the OPD was at least in part responsible for the reported trend.…”
mentioning
confidence: 99%
“…Multiple studies have looked at payments to otolaryngologists since the induction of the CMS Open Payments database [6][7][8][9] ; however, no study has performed an in-depth investigation of these payments based on product type. Morse et al classified payments to otolaryngology subspecialties by reviewing the companies' website for products they generally produce.…”
Section: Introductionmentioning
confidence: 99%